Improving Airplane E-ticket Purchasing Decisions Through Social Media Marketing Instagram and Ease of Use of Online Travel Agent Applications in Indonesia Mediated by Trust - Edhie Budi Setiawan; Dian Artanti Arubusman; Atong Soekirman; Peppy Fachrial; Indriani Maysandra (Politeknik APP Jakarta, 2024)
This study aims to ascertain how social media marketing (such as Instagram) and ease of use affect consumer decisions, as well as how trust functions as a mediating factor in the relationship between social media marketing and ease of use and consumer decisions. There are two types of data that are used; primary data are gathered through questionnaires, and secondary data are gathered from books and journals. This study used probability sampling techniques with a simple random sampling method, namely with 170 respondents. The analysis method in this study uses SEM-PLS (Structural Equation Model - Partial Least Square). This study's findings indicate that trust has a major impact on purchase decisions, simplicity of use has a large impact on decisions, and social media marketing has no significant impact on decisions. Ease of use and social media marketing's influence on purchase decisions might be mitigated by the trust factor. If respondents trust online travel brokers, social media marketing will have an impact on their purchase decisions.